Spiritual and cognitive origins and sources of knowledge of "Akhuns" and "Ishans" in the Kazakh steppe (Eurasian Journal of Religious Studies, 2023)
The article outlined the tasks of studying the concepts of Akhun and Ishan, and conducted historical research on the spiritual sources and levels of knowledge from which they were taught. It has been shown that they come mainly from teachings dating back to the XIҮ-XҮ centuries. Having briefly analyzed the Sufi doctrine and its mysticism, we mentioned the main representatives. The naqshbandia branch of Sufism and its basic principles were demonstrated, religious philosophical worldview orientations were analyzed, religious educational institutions, Bukhara, Samarkhan, Tashkent, Khiva, Khorezm, Turkestan, Karnak, UFA, Istanbul, Baghdad, Cairo madrasas and directions of education were presented. We gave examples of the content of education in the masses, educational programs. In particular, along with religious teachings, we studied linguistics, logic, jurisprudence, medicine, literature, etc. We showed the general directions of knowledge acquired by akhuns and ishans in the Kazakh steppes. As a result, conclusions were drawn about their merits to the Kazakh steppe and significant work in the field of enlightenment.
Keywords: Akhun; Ishan; Madrasa; Sufism; Naqshbandiya